Arthur and the Bad-Luck Brain - Krensky, Stephen (New York : Little, Brown, 2003)
The Brain does not believe in superstition, but when he tries to prove that superstitions are nonsense he starts finding bad luck everywhere he turns.
3.0.
360
Accelerated Reader AR
Keywords: Superstition -- Fiction; Aardvark -- Fiction; Animals -- Fiction